A comprehensive phenotypic characterization of a whole-body Wdr45 knock-out mouse - Caroline A. Biagosch; Silvia Vidali; Michael Faerberboeck; Svenja-Viola Hensler; Lore Becker; Oana V. Amarie; Antonio Aguilar-Pimentel; Lillian Garrett; Tanja Klein-Rodewald; Birgit Rathkolb; Enrica Zanuttigh; Julia Calzada-Wack; et al. (Mammalian Genome, 2021)
Pathogenic variants in the WDR45 (OMIM: 300,526) gene on chromosome Xp11 are the genetic cause of a rare neurological disorder characterized by increased iron deposition in the basal ganglia. As WDR45 encodes a beta-propeller scaffold protein with a putative role in autophagy, the disease has been named Beta-Propeller Protein-Associated Neurodegeneration (BPAN). BPAN represents one of the four most common forms of Neurodegeneration with Brain Iron Accumulation (NBIA). In the current study, we generated and characterized a whole-body Wdr45 knock-out (KO) mouse model. The model, developed using TALENs, presents a 20-bp deletion in exon 2 of Wdr45 . Homozygous females and hemizygous males are viable, proving that systemic depletion of Wdr45 does not impair viability and male fertility in mice. The in-depth phenotypic characterization of the mouse model revealed neuropathology signs at four months of age, neurodegeneration progressing with ageing, hearing and visual impairment, specific haematological alterations, but no brain iron accumulation. Biochemically, Wdr45 KO mice presented with decreased complex I (CI) activity in the brain, suggesting that mitochondrial dysfunction accompanies Wdr45 deficiency. Overall, the systemic Wdr45 KO described here complements the two mouse models previously reported in the literature (PMIDs: 26,000,824, 31,204,559) and represents an additional robust model to investigate the pathophysiology of BPAN and to test therapeutic strategies for the disease.